THE NATURE OF EDUCATORS IN ISLAM - Zulham Zulham (Universitas Dharmawangsa, 2020)
Abstract: Islam has confirmed in the Koran that every human being created by Allah Swt has his potential and this potential dominates in every person. This dominating potential should be developed by humans to easily achieve the desired goals. As an example of the potential to educate, indeed every human being is gifted by Allah to be able to educate, either educating himself or others, but this potential is possessed by someone mediocre. There are several terms or lafadz in Arabic which contain the meaning of educator, these words are not only limited to language, but also contained in the verses of the Koran. Here are some of the educator lafadz found in the Koran, including mu'allim, mudarris, murabbi, and ad-Dzikru. The words or lafadz listed in the Koran indicate the degree and main duties of the educator in accordance with the lafadz they carry. To become the best educator who can produce reliable students, every educator must be able to develop the educational potential that is in him as much as possible, and he must be able to believe that the potential for education is more dominant in him when Allah Swt first gives nature or outward potential to him. As explained by Imam Zarkasyi, the spirit of an educator is more important than the educator himself